How to train your dragon book 12 : how to fight a dragon$1 (Bs fury /s - Cowell, Cressida (New York : Little, Brown and Company, 2017)
In the epic finale, Hiccup Horrendous Haddock III must face the Dragon Furious and fulfill his destiny to unite humans and dragons$1 (Bor witness the end of both species.s
Originally published in the U.K. by Hodder Children$1 (Bs Books, 2015.s
Keywords: Vikings -- Fiction; Dragons -- Fiction; Quests (Expeditions) -- Fiction; Friendship -- Fiction; Fathers and sons -- Fiction; Betrayal -- Fiction; Humorous stories